Diversity of enteroviruses from cerebrospinal fluid specimens collected from hospitalised patients in the private and public sector - Van Zyl, Walda B. (University of Pretoria, 2022)
Dissertation (MSc (Medical Virology))--University of Pretoria, 2021.